Exploring the Architectural Identity and Culture of the Ikwerre Ethnic Group in Rivers State, Nigeria - Adibe Nkeiruka Okwakpam; Imaah Napoleon Ono; Brisibe Warebi Gabriel; Daminabo Frank Ferdinand (International Journal of Rural and Regional Development, 2024)
This paper investigates the architectural identity and culture of the Ikwerre ethnic group in Rivers State, through an analysis of traditional practices, spatial organization, and structural forms. This paper provides insights into the relationship between Ikwerre Architecture and Ikwerre culture. The study highlights the unique attributes of Ikwerre identity as expressed in their built environment and cultural practices, to establish the key features of Ikwerre Architectural identity and culture. A mixed-method research design approach was employed for the study. A sample size of 400 respondents was selected and the data was concerned with the frequency and categorical distribution of the participants based on specific demographic characteristics such as gender, qualification, status, years of experience, and age. The findings indicate a noteworthy agreement among respondents regarding specific architectural features such as Obiri Oro and Obiri Oha ( family and community halls), Obokoro, Egelege (Village Square ), Ahia (Market), meeting spaces, courtyard designs, compound layouts, centralized head of family’s house, Farmlands, decorative murals, the use of Uli (color pigment), cowries and plates to decorate walls contribute to the architectural identity of the Ikwerre people while these cultural practices such as language, dressing, traditional religion, cultural festivals, Men and Women meetings, cultural celebrations, arts and craftsmanship, dance and music, farming, and oral tradition (proverbs, storytelling, and songs) contribute to the cultural identity of the Ikwerre people in Rivers State. This study recommends that the relationship between Ikwerre Architecture and culture should be sustained to promote Ikwerre Architectural identity. Architecture as a tool to portray identity, the Ikwerre communities would not be void of identity. By incorporating traditional elements into architectural forms, built environments can effectively preserve and convey the essence of Ikwerre culture for future generations, thereby contributing to the ongoing discussion on cultural preservation
Keywords: Architecture; Culture; Ikwerre ethnic group; identity